Población, encomienda, territorio: Manzanares a finales del siglo XV - Almagro Vidal, Clara (En la España Medieval, 2008)
An approach to the evolution of Manzanares (Ciudad Real) based on new documents found in the Archivo de la Chancillería de Granada, referring to the delimitation of its boundaries in the fifteenth century. Diverse reflections are posed regarding the origins of the settlement, the formation of its territory and the relation of both the settlement and its territory to the Calatrava encomienda instituted there.